Fostering collaborative approaches for sustainable tourism development on Bawean Island - Durratun Nashihah; Akbar Pandu Dwinugraha; Reza Eka Lestari; Fitri Ayu Puspaningrum (JRTI (Jurnal Riset Tindakan Indonesia), 2024)
This research focuses on the role and collaboration of stakeholders in developing sustainable tourism on Bawean Island, an area with very high natural and cultural potential. Sustainable tourism is defined as efforts that support a balance between environmental preservation, socio-cultural development, and economic benefits. This paper investigates the role of stakeholder collaboration in advancing sustainable tourism development on Bawean Island. It emphasizes the necessity of integrating community involvement, effective local governance, strategic planning, and continuous education to create a sustainable tourism framework that benefits both the local population and the environment. It also discusses the critical role of regional governance in facilitating dialogue among stakeholders and ensuring accountability in tourism planning. This study uses a qualitative descriptive approach, a comparative case study method, and a logical framework approach to analyze interactions between the government, the private sector, local communities, and academics. The research results show the importance of face-to-face dialogue, trust building, Commitment to the process, shared understanding, and intermediate outcomes for successful collaboration. Even though there are still obstacles, such as limited infrastructure and lack of initial coordination, efforts are emerging to overcome these challenges through a structured, collaborative approach so that tourism development on Bawean Island can achieve long-term economic, social, and environmental sustainability. The findings suggest that through collaborative strategies, Bawean Island can develop a sustainable tourism model that preserves its unique cultural and natural heritage while enhancing the socio-economic well-being of its residents.